Intraperitoneal cerebrospinal fluid pseudocyst with ventriculoperitoneal shunt - Mohammad Sadegh Masoudi; Marziye Rasafian; Zahra Naghmehsanj; Fariborz Ghaffarpasand (Wolters Kluwer Medknow Publications, 2017)
Ventriculoperitoneal (VP) shunting is mostly used in the treatment of hydrocephalus and many complications have been reported with this method. Abdominal Pseudocyst (APC) are relatively uncommon but important complications in patients with VP shunts. We herein report the case of a 9-year-old boy with VP shunt who presented with abdominal distension, abdominal pain, malaise, and decrease of appetite. Abdominal pelvic computed tomography confirmed a diagnosis of APC. Laparotomy was done and VP shunt was placed into the other side of peritoneal cavity again. Also here, etiology, presentation, diagnosis, and treatment of APC were reviewed.